Colorectal Cancer and Basement Membranes: Clinicopathological Correlations - Charalampos C. Mylonas; Andreas C. Lazaris (Gastroenterology Research and Practice)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer in males and the second in females. In 2008, an estimated 1.2 million people were diagnosed with and 608,700 people died of CRC. Besides diagnosis and treatment, prognosis is an important matter for cancer patients. Today, clinicopathological correlations have many applications in cancer prognostication. Examples include the prediction of the medium patient survival and the screening for patients suitable for specific therapeutic approaches. Apart from traditional prognostic factors, such as tumor stage and grade, new markers may be useful in clinical practice. Possible markers may result from the study of basement membranes (BMs). BM seems to play a role in the pathogenesis of colorectal cancer, so BM alterations may have prognostic significance as well. The purpose of this review is to briefly describe BMs and their relationship with CRC, in the aspect of clinicopathological correlations.